Studies on the Estimation of Pregnancy Rate of White Hanwoo (Albino Korean Native Cattle) with Sexed Semen - Sung Woo Kim; Jinseok Choi; Changyoung Choe; Dongkyo Kim; Yeoung-Gyu Ko; Chungsil So; Hwan-Hoo Seong (The Korean Society of Animal Reproduction and Biotechnology, 2015)
The purpose of this study is to produce wanted sex progeny of genetically confined White Hanwoo (albinism) with preselected sex sperm. One bull of White Hanwoo was chosen for semen donor and X sperm was sorted by MoFlo XDP cell sorter. To compare the pregnancy and birth rates, KPN straw was used as control, total number of unsorted sperm was 20×106/straw. Sexed X frozen semen with 2×106 cells or 4×106 cells per straw were in seminated twice on Hanwoo heifers. The abnormality of the sexed X semen was 24.9 ± 7.31% and distal reflex abnormality of mid piece was significantly (p<0.05) higher (11.7%) compared with that of KPN 768 (5.6%). There were no differences on the pregnancy and birth rates between 2×106 cells or 4×106 cells of X-sperm but KPN semen showed significant differences (p<0.05). The pregnancy rates of KPN 768, 2×106 cells and 4×106 cells X-sperm of White Hanwoo cattle were 85.0%, 26.3% and 50%. The birth rates were 80.0%, 15.8% and 21.4%, respectively. The female offspring rates of KPN 768, 2×106 cells and 4×106 cells X-sperm of White Hanwoo cattle were 43.8%, 100% and 100% (p<0.05). These results indicated that sex sorted White Hanwoo could be used for the production of wanted progeny with 2×106 cells/straw for AI. To increase the efficiency of calf production, the sperm number of sex sorted semen will be optimized for sex selection of White Hanwoo progeny.